Mathematical Literacy in Algebra Content: The Trajectory of Students Conceptual Cognitive Style - Ramadanti, Andi Vitrah; Rahman, Abdul; Upu, Hamzah (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study intends to describe the process of students' mathematical literacy in algebra content with a conceptual-tempo cognitive style. We employed a descriptive qualitative research approach. We conducted this research at public high school 23 in Makassar. The MFFT (Matching Familiar Figure Test) helped us choose the people who would be in the study because it finds students with a conceptual tempo cognitive style. The data collection technique uses instruments in the form of mathematical literacy test sheets, interview guidelines, and documentation. This study employs a qualitative data analysis technique. The study's findings showed that students who learned to think quickly and correctly were able to answer level II and IV questions by completing three parts of the literacy process: formulating, using, interpreting, and evaluating. Students with an impulsive cognitive style in solving level II and IV questions were only able to fulfill 1 aspect of the literacy process, namely the aspect of formulating. Students with a reflective cognitive style are capable of addressing three aspects of the literacy process, which include formulating, using, interpreting, and evaluating information. Additionally, students with a slow, inaccurate cognitive style in completing level II and IV questions are only able to fulfill 1 aspect of the literacy process, namely the aspect of formulating.